Elaboração de uma célula de testes para motores a combustão interna - Aquino, Iago Mateus Sá (Universidade Federal Rural do Semi-Árido, 2018)
according to the Ministry of Environment. Being these engines the main driving force of light and heavy vehicles, motorcycles, machines and generators, it is clear the necessity of engines increasingly efficient, with higher yield and less pollutants and for that a strong improvement bias are the cells of combustion engine tests, which can generate and capture information of inestimable value to meet these objectives. It is necessary to generate the proper instruction about the operation of an internal combustion engine and its nuances in order to build a first step of a solid enough knowledge to understand and be able to generate interpretation of the data arranged by the cell promoting improvements not only in the engines, but in all of its components, peripherals and other elements involved, such as lubricating fluids, cooling fluids and fuels. The results obtained make possible the conversion of the theoretical knowledge into empirical, being perceptible the relationship between the analyzed parameters and some factors that can exert influence on these, which were analyzed from the acquisition and registration of the data displayed by the cell. It was also possible to improve the perception of how an internal combustion engine works in close contact with the engine and the construction and assembly of all the peripherals, systems and subsystems that are fundamental to its operation. The tests bring results that confirm the theoretical basis of the work and provide a series of possibilities of subsequent work and improvements in the own cell or bench of experimental tests with motors.
Monografia
Keywords: Máquinas térmicas; Motores a combustão interna; Testes de motores; Bancada de testes para motores; Células de testes de motores; Thermal machines; Internal combustion engines; Engine tests; Engine test cells; Test bench for engines; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA